A Full Chain of Applying Struvite Recovered from Biogas Slurry to Promote Vegetable Growth - Yunhan Li; Wei Wang; Linhe Sun; Jian Cui; Xiaojing Liu; Jixiang Liu; Yajun Chang; Dongrui Yao (Agriculture, 2025)
The expansion of the livestock industry has led to an increase in biogas slurry discharge, which contains high levels of nitrogen (N) and phosphorous (P). Struvite precipitation is an effective method for the recovery of N and P from biogas slurry, and the recovered N and P can be applied as a slow-release fertilizer in agricultural production. To form an industrial chain for struvite recovery and application in agriculture, we investigated the factors affecting struvite recovery from biogas slurry generated on a pig farm and evaluated its efficacy as a fertilizer. The N and P recovery efficiency was higher when magnesium chloride (MgCl2) was used as a magnesium (Mg) source compared with magnesium oxide (MgO), and the optimal reaction conditions were pH 10, a reaction time of 20 min, a stirring rate of 200 rpm, and a Mg/P/N ratio of 1.2:1.0:1.0, which achieved N and P recovery rates of 81.83% and 99.67%, respectively. To further investigate the commercial utility of using struvite recovered from biogas slurry as a fertilizer, the growth and content of nutrients in two common vegetables in China were measured. The vegetable quality-related parameters of bock choy (Brassica chinensis) improved as the proportion of struvite in the fertilizer increased. Fresh weight, soluble sugar, and soluble protein increased by 194.47%, 46.13%, and 82.42%, respectively. The quality-related parameters of water celery (Oenanthe javanica (Blume) DC.) increased with an increasing proportion of struvite (27.90 mg·g−1 soluble sugar and 42.20 mg·g−1 soluble protein). The application of struvite precipitated from biogas slurry in plant cultivation shows great potential and lays a solid foundation for the resourceful recovery and utilization of biogas slurry.